The Post Truth and God - Naranjo Navas, Christian Paúl (Revista de Filosofía, 2020)
The article attempts to visualize the dangers of the post-truth era, while relativizing the relative to argue that the postulates of this era are irrational. The only way to understand a moral structure in a post-truth society is through imposition, persuasion or manipulation. In all cases, morality is relegated to the subjective. The argument is constructed based on the law of non-contradiction, stating that the truth exists, and its characteristics are universal, static and logical.